[BP.09.01] ASSESSMENT OF LEFT VENTRICULAR SYSTOLIC FUNCTION IN MASKED AND ISOLATED OFFICE HYPERTENSION IN A GENERAL POPULATION IN NORTHERN ITALY: THE VOBARNO STUDY. (September 2017) - Salvetti, M.; Paini, A.; Stassaldi, D.; Bertacchini, F.; Maruelli, G.; Rubagotti, G.; Favro, S.; Riviera, M.; Dallapellegrina, L.; Rosei, E. Agabiti; Muiesan, M.L.
Abstract : Objective: Previous studies have demonstrated that ambulatory blood pressure monitoring (ABPM) provides useful information in hypertensive patients and in the general population. Few data are available on LV function according to BP categories as defined by clinic and 24 hours BP measurement. The aim of our study was to evaluate indices of left ventricular (LV) function in normotensive subjects (NT), in patients with isolated office hypertension (IOH), with masked hypertension (MHT) and with sustained hypertension (HT) defined according to clinic and 24 hours blood pressure (BP) monitoring. Design and method: Out of 585 subjects, we identified 294 untreated subjects (mean age 56 ± 9 years, 45% males) participating in our ongoing population study (Vobarno study). All subjects underwent standard laboratory examinations and clinic and 24 hours blood pressure measurement. Standard echocardiography was performed in all patients, and indices of systolic function were calculated. Furthermore in all patients, myocardial mechanoenergetic efficiency (MEE) was calculated as stroke volume/heart rate and indexed to LV mass (MEEi = MEE/LVM)(de Simone et al, 2016). Results: 39.5% of subjects were classified as NT, 17% as IOH, 18.5% as MH and 25% as HT. MEEi was significantly lower in IOH, MH and HT as compared to NT (0.52 ± 0.12, 0.54 ± 0.13, 0.51 ± 12 vs 0.67 ± 0.16 ANOVA p < 0.05). The difference between groups remained statistically significant after adjusting for all possible confounders. Midwall fractional shortening (absolute value and % of predicted), was significantly lower in IOH, MH and EH as compared to NT, while no differences in fractional shortening and ejection fraction were observed among the four groups of subjects. Conclusions: Left ventricular myocardial mechanoenergetic efficiency and midwall function are depressed not only in patients with sustained hypertension, but also in patients with isolated office and masked hypertension.